Physics Higher Order Thinking Skills Analysis: Motion at Secondary School - Oktavianty, Erwina; TMS, Haratua; Sirait, Judyanto; Supriadi, Yetti (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This study aimed to analyze students ability to solve Higher Order Thinking Skills (HOTS) problems in physics, especially in motion in one of Pontianak’ Senior High School. The methods used in this research was descriptive method with qualitative approach. The subjects in this research is 125 students of class XI MIPA. The data-collecting instruments in this research was twenty multiple choices problems, consists of analyze, evaluate, and create step of thinking. According to the data result of this research, it can be seen that the average of students ability in solving higher order thinking skills problems is 32.27%. Specifically, in each dimension of HOTS problems are analyze problems 43,13%, while evaluate ability are 41% and create ability are 12.67%. Those results show that students abilities of solving high order thinking problems still categorised as low. The result of mann-whitney were asymp. Sig. (2-tailed) score of 0,170 (>0,05), so H0 are accepted and H1 are denied. It means that there are no significant difference between male and female students in term of ability to accomplish higher order thinking problems. Therefore, learning activities in order to increase students high order thinking skills are needed at secondary school in Pontianak.